2013 17th European Conference on Software Maintenance and Reengineering 2013
DOI: 10.1109/csmr.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Bug Reports and Bug Fixing in Open Source Android Apps

Abstract: Abstract-Smartphone platforms and applications (apps) have gained tremendous popularity recently. Due to the novelty of the smartphone platform and tools, and the low barrier to entry for app distribution, apps are prone to errors, which affects user experience and requires frequent bug fixes. An essential step towards correcting this situation is understanding the nature of the bugs and bug-fixing processes associated with smartphone platforms and apps. However, prior empirical bug studies have focused mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…As noted in Section 1, with security being seen as central to user perceptions of software quality [4], leading in part to growing interest in the security of mobile OSs [12,14], it would seem timely to explore and provide understandings for the nature of Android security-related issues, how stakeholders' views covary, and various users' preferences and priorities with respect to changes. Such insights would provide indirect understandings around the attention that is given to such issues by the community.…”
Section: Background and Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in Section 1, with security being seen as central to user perceptions of software quality [4], leading in part to growing interest in the security of mobile OSs [12,14], it would seem timely to explore and provide understandings for the nature of Android security-related issues, how stakeholders' views covary, and various users' preferences and priorities with respect to changes. Such insights would provide indirect understandings around the attention that is given to such issues by the community.…”
Section: Background and Questionsmentioning
confidence: 99%
“…For instance, Zaman et al [4] compared developers' focus on security and performance bugs in Firefox and found that security bugs were favored for fixing over those that were performance-related, and were fixed much more quickly. Critical security bugs have also been removed from the Android issue list to avoid or reduce exacerbation or exploitation of such issues [12].…”
Section: Background and Questionsmentioning
confidence: 99%
“…al. [24] concluded that most Android bug reports for open source apps are of high-quality, however in their study only ≈ 46% of bug report contained steps to reproduce, and even fewer (≈ 20%) contained additional information (e.g. bug-triggering input or even an app version).…”
Section: Bug Reporting Studiesmentioning
confidence: 99%
“…Furthermore, Android's very rapid evolution has not been replicated by other mobile OS projects [28], and so, this may affect the generalizability of our findings. That said, the classification scheme used for studying NFRs issues is applicable to all software projects [64]. Furthermore, although the issue tracker of many mobile OSs are not publicly available, and the distribution of these OS issues may not be similar to what is observed in this work for Android OS, mobile OS like Microsoft Windows, Apple iOS, Symbian and BlackBerry are all likely to follow release-maintenance cycles similar to that of Android OS in order to improve their offerings.…”
Section: Limitationsmentioning
confidence: 99%